An overview on the present status and future prospects of demersal finfish resources in India - Bensam, P (Indian Journal of Fisheries, 2011)
Wilh the introduction of mechanized bottom trawling from the late fifties, the exploitation of demersalfrnfishes atuined a 2.7- fold increase during late eighties (0.52 million tonnes). But the proportion ofproduction went down from about 32% of the total in 1981 to about 22% in late eighties. The resourceswhich were exploited to the optimum in the 0-50 m dq>th zone during 1985-89 were sdaenids, silverbellies, elasmobranchs, pink perch, lizard fishes, goat fishes, threadflns, eels, etc. As a result of intensivecoastal trawling and introduction of gears such as purse seines, resources like catfishes, the whitefish, dara,karkara, koth, ghol, warn and flaiheads declined in production. This was chiefly due to recruitment over -fishing resulting from the destmction of juveniles as well as the trampling of the bottom habitat. As perrecent estimate, only a marginal increase in production of demersal finfishes from the presently exploitedzoie was possible, whereas from the deeper waters about 300 000 tonnes consisting of elasmobranchs,major perches, pink perch, catfishes, lizard fishes, etc appeared possible. For the efficient exploitation andutilization of these resources to be harvested, it is essential to develop adequate infrastructure facilities, postharvest technology, value-added products, domestic marketing and exporL Since the large-scale bottomtrawling has been leading to deleterious effect on certain vulnerable finfish resources, there is inuninentneed for imposing certain controls on fishing in the inshore waters.